Polarimetric C-band Microwave Scattering Properties of Snow Covered First-Year Sea Ice ... - Gill, Jagvijay P. S. (Graduate Studies, 2015)
In this thesis, the physical, dielectric, and C-band polarimetric microwave properties of snow covered first-year sea ice (FYI) at different temperature conditions, largely encompassing late winter to melt onset period are investigated. First, a set of polarimetric parameters derived using different decomposition and synthesis techniques are analyzed at cold temperature conditions by relating them to pre-identified sea ice types. These parameters are further analyzed for their sea ice classification potential. This analytical scheme is extended to warmer temperature conditions and their stability for ice type signature response and classification potential is assessed. Second, the polarimetric SAR response from snow covered FYI at cold temperature conditions is analyzed to investigate the sensitivity of polarimetric backscatter to snow thickness. The backscatter sensitivities are examined as a function of change in surface air temperature through the changes manifested in snow geophysical properties. Lastly, ...